Parameter identification of strain rate dependent hardening for sheet metals - Söhngen, Benjamin; Willner, Kai (Proceedings in Applied Mathematics and Mechanics, 2019)
Abstract In this contribution we examine the influence of strain rate on the isotropic hardening of two sheet metals. The nominal strain rates vary between 0.0005 s−1 and 20 s−1 and the full field deformation is captured with the help of digital image correlation (DIC) technique. For modelling the strain rate dependent behaviour, we introduce a rate dependent part in the definition of the hardening stress, distinguishing between approaches that incorporate the rate dependency in an additive or multiplicative manner. The hardening laws are thereby embedded in a large strain plasticity framework based on the logarithmic strain space. The material parameters are identified both in a “direct” fashion, where the gap between constitutive equation and measured stress-strain curve is minimized and inverse, by using the finite element method (FEM) to generate force-displacement curves and the virtual fields method, which compares internal and external virtual work.